DESAIN PEMBANGUNAN PASAR DENGAN FASILITAS RAMAH LINGKUNGAN DI KELURAHAN TALANG PUTRI - Nugraha, Ivan x; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The design of the market development with environmentally friendly facilities in Talang Putri Village aims to create a public space that meets the economic needs of the community while considering environmental sustainability. This study uses a qualitative approach, utilizing case studies and field observations to gather data on the existing market conditions and the needs of the community. The results indicate that the implementation of Green Architecture principles, including effective waste management and natural lighting optimization, significantly enhances the market’s functionality and sustainability. Additionally, the market will be equipped with designated areas for public zones, service zones, private zones, and semi-public zones to ensure comfort and cleanliness. In conclusion, it is expected that this market will become a clean, comfortable, and eco-friendly center for economic activities for the surrounding community.Keywords : Environmental-Friendly Market Design, Green Architecture, Environmental Sustainability, Effective Waste Management.